Sucrose concentrations on in vitro growth of Tillandsia geminiflora Brongn. (Bromeliaceae) plantlets - Pinto, A. C.R. [UNESP]; Demattê, M. E.S.P. [UNESP]; Santos, D. M.M. [UNESP]; Barbosa, J. C. [UNESP]; Creste, S. A. (My University, 2015)
Tillandsia geminiflora is a bromeliad with ornamental value. In Brazil this species is under the threat category of vulnerable. The slow growth and low multiplication rate lead to illegal over-collection in the wild to meet commercial demands. Protocols for in vitro propagation of T. Geminiflora can speed growth and increase multiplication rate. In tissue culture media sucrose is usually added to support in vitro growth and promote organogenesis. Also it can play an important role as osmotic agent. The optimum level of sucrose may vary according to species, explant source and stage of development. There is no report about optimum sucrose level for initial growth of T. Geminiflora plantlets. Also, in vitro culture of T. Geminiflora may require specific needs, due to their epiphytic habit. The present study evaluated sucrose concentrations on initial growth of plantlets in vitro. Seeds were germinated in 1/4 MS medium without sucrose. After 90 days, plantlets were recultured to 3/4 MS medium added with sucrose (0, 3.75, 7.5, 15.0, 22.5, 30.0 and 60.0 g/L). The experiment was conducted in complete randomized design, with treatments having four replicates (one culture flask/replication and six plantlets/flask). Seed germination and green plantlets development were achieved in 1/4 MS medium without sucrose for 90 days. However, plantlets maintained in media without sucrose, for 120 days, showed high water content and were completely translucent due to leaves' chlorophyll loss. These plantlets were significantly shorter and showed lower dry mass compared to plantlets maintained in media added with sucrose. Polynomial regression analysis for sucrose concentration and plantlets dry mass was significant, showing that 50.0 g/L of sucrose produced plantlets with the highest dry mass. Over this predicted concentration was observed a decrease in the value of dry mass, showing the effect of sucrose on the inhibition of growth.
Keywords: Early plantlets growth; Endangered bromeliad; Micropropagation